Pharmacotherapy of traumatic childhood aphasia: beneficial effects of donepezil alone and combined with intensive naming therapy - Dávila, Guadalupe; Moyano, María Pilar; Edelkraut, Lisa; Moreno-Campos, Lorena; Berthier, Marcelo L; Torres-Prioris, María José; López-Barroso, Diana (Frontiers Media, 2020)
Currently, language therapy is the only treatment for childhood aphasia (CA). This study explored using the cognitive-enhancing drug donepezil (DP) to improve language recovery in a 9-year-old girl with chronic anomic aphasia caused by left temporal-parietal brain injury. The study involved DP treatment alone, combined with intensive naming therapy (INT), and washout periods. Results showed that DP alone improved spontaneous speech, comprehension, repetition, and attention, while combining DP with INT further enhanced naming abilities. Improvements remained after treatment, and DP had no side effects, enabling the child to return to regular schooling. Further research is needed to confirm these findings.
Keywords: Quimioterapia; Afasia; Niños -- Enfermedades; Anomia; Childhood aphasia; Donepezil; Intensive naming therapy; Language; Pharmacological treatment; Traumatic brain injury